Vacuum - assisted closure (VAC) dressing therapy for the management of wounds: Our experience in rural set up - Kedar Gorad; Moses Ingty; Gautam Taralekar (Al Ameen Medical College, 2020)
Introduction: Vacuum-Assisted Closure (VAC) uses negative pressure to assist wound healing. Negative pressure drains fluid from the wound, thus removing the substrate for growth of microorganisms. Negative pressure may also accelerate granulation tissue formation and promote angiogenesis. The mechanical stimulation of cells by tensile forces may also play a role by increasing cellular proliferation and protein synthesis. Negative Pressure Wound Therapy (NPWT) involves the use of a negative pressure therapy or suction device to aspirate and remove fluids, debris and infectious materials from the wound bed to promote the formation of granulation tissue. Material and Methods: A total o 25 cases of ulcers between August 2019 and June 2020 were taken for study. Out of 25 patients 18 were males and 7were females, Mean age ranging from 22 to 70 for males and 18 to 57 for females. In our study, maximum cases reported were diabetic ulcers 19 (76%), road traffic accidents 4 (16%) patients and 2 (8%) patients had mechanical injury. Results: Out of 25 wounds in the study, 20 wounds reduced in area and cured with split thickness skin grafting and 5 wounds were reduced in area and healed after secondary suturing. All wounds were infected before VAC treatment. After VAC dressing, almost all wounds became swab negative, no patient required surgical debridement and there was gradual decrease in size of wound. Wound healing was better in the controlled diabetic group compared to uncontrolled diabetic group. Commonest organisms isolated were Staphylococcus, Pseudomonas and Proteus. Conclusion: VAC dressing provides sterile and controlled environment to large wound surfaces by controlled application of sub-atmospheric pressure and prepares wounds for closure through split skin grafting and secondary closure in short time leading to less overall morbidity with decreased hospital stay. In our study, VAC therapy promotes granulation tissue formation leading to faster wound healing and speedy recovery. VAC is promising technique in wound healing. It can be used in all types of wound.